Mouse hepatitis virus strain UAB infection enhances resistance to Salmonella typhimurium in mice by inducing suppression of bacterial growth. - Fallon, M T (1991)
We have previously shown that intranasal infection of mice with mouse hepatitis virus (MHV) strain UAB (MHV-UAB) increases their resistance to Salmonella typhimurium injected intravenously 6 days later. To study how salmonella resistance was induced, BALB/cAnNCr mice were infected with salmonella strains carrying specific genetic alterations. One set of studies compared the effect of MHV infection on subsequent salmonella infections with AroA- (avirulent) and Aro+ (virulent) salmonellae. Unlike its effect on Aro+ salmonellae, MHV failed to reduce the number of AroA- salmonellae recovered from mice. Because AroA- S. typhimurium shows almost no growth in vivo, this failure indicated that the effect of MHV on salmonella resistance required growth of the infecting salmonellae. In other studies, the effect of MHV infection on both growth and killing were monitored simultaneously in mice with growing salmonellae carrying a single copy of the temperature-sensitive pHSG422 plasmid, which is unable to replicate in vivo. MHV infection reduced salmonella growth but caused no increase in salmonella killing. MHV infection of mice given wild-type salmonellae also resulted in no increase in salmonella killing 4 h after salmonella challenge. These studies demonstrate that MHV-UAB infection increases host resistance to salmonellae by enhancing suppression of bacterial growth instead of by increasing the amount of salmonella killing.